Friction and wear behavior of direct metal deposition on Suh3 - Choi, Byungjoo; Cho, In Sik; Jung, Do Hyun; Lee, Moon G.; Jeon, Yongho (Archives of Metallurgy and Materials, 2019)
Poppet valves made from high-frequency heat-treated SUH3 steel have insufficient durability, and scratches appear on the valve face in prolonged use. It is necessary to develop surface treatment technology with excellent durability to prevent the deterioration of engine performance. Therefore, a surface treatment technology with higher abrasion resistance than existing processes was developed by direct metal deposition to the face where the cylinder and valve are closed. In this study, heat pretreatment and deposition tests were performed on three materials to find suitable powders. In the performance evaluation, the hardness, friction coefficient, and wear rate were measured. Direct metal deposition using Inconel 738 and Stellite 6 powders without heat pretreatment were experimentally verified to have excellent durability.
Keywords: Direct metal deposition; Engine performance; Friction and wear behaviors; Friction coefficients; Friction test; Heat pretreatment; Surface treatment technology; Wear test; Direct metal deposition; Friction test; Heat pretreatment; Micro-hardness; Wear test